2020
DOI: 10.1111/pedi.13081
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of renin‐angiotensin system markers in youth with type 2 diabetes and associations with renal outcomes

Abstract: Aims/hypothesis: Youth with type 2 diabetes (T2D) have high rates of obesity, hypertension and suboptimal glycemic control. We hypothesized that reninangiotensin system (RAS) activation is present in youth with T2D and associated with poor glycemic control and renal outcomes. Methods: Cross-sectional analysis of 183 youth with T2D and 100 controls from the Improving renal Complications in Adolescents with T2D through REsearch cohort. Diabetes youth stratified by urine albumin:creatinine ratio (ACR) < or ≥2 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Measures of intra-renal RAS activity and systemic RAS activity may not always be concordant, as noted in studies by Brenner and coworkers [ 64 ]. We have also found inconsistencies between systemic and renal measures of the RAAS in our recent studies of youth with type 2 diabetes that limit interpretation [ 65 ]. Serfero et al have suggested that the production of Ang-(1–7) from Ang II in the circulation is independent of ACE2 [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measures of intra-renal RAS activity and systemic RAS activity may not always be concordant, as noted in studies by Brenner and coworkers [ 64 ]. We have also found inconsistencies between systemic and renal measures of the RAAS in our recent studies of youth with type 2 diabetes that limit interpretation [ 65 ]. Serfero et al have suggested that the production of Ang-(1–7) from Ang II in the circulation is independent of ACE2 [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…65, P < 0.0001; Fig8A) in men, but the relationship was not significant in females (r = -0.29, P = 0.08; Fig8B). Our analysis showed a similar difference between males and females in the relationship between ACE2 expression and CCL2 expression (Fig 8Cand 8D).…”
mentioning
confidence: 90%
“…However, there is no direct evidence that recombinant ACE2 binds and neutralizes SARS-CoV-2. Patients with hypertension, diabetes, or obesity present the major risk group for COVID-19 and are characterized by high levels of sACE2 [ 11 , 12 , 13 , 14 ]. These findings suggest that sACE2 is unable to bind and neutralize SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Renal injury is a frequent complication in adolescents with type 2 diabetes 30 31 and predicts long-term chronic kidney disease. 32 Significant weight loss, secondary to bariatric surgery, is associated with resolution of proteinuria in adolescents with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%